2018
DOI: 10.1177/0002764218768862
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Social and Solidarity Economy Sector in Greece, Spain, and Switzerland in Times of Crisis

Abstract: In the context of the recent economic crisis and rising inequality, interest in the Social and Solidarity Economy (SSE) as a viable alternative economic model has gathered pace in Europe. This article, based on an innovative content analysis approach of organizations’ websites from the LIVEWHAT project, provides a snapshot of the SSE sectors’ main features in three European countries, namely Greece, Spain, and Switzerland, to understand how the SSE is practiced in varying contexts, uniquely affected by the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 9 publications
0
9
0
1
Order By: Relevance
“…Some participants feel that diversity should be part of a global policy that is integrated and institutionalized as well as interdepartmental and horizontal—which is to say, collectively borne and implemented in a decentralized manner (Lee-Gosselin et al, 2013). Secondly, participants see solidarity in initiatives intended to democratize the economy through citizen action, particularly local agriculture, fair trade, or solidarity-based financing (Kalogeraki et al, 2018). Thirdly, participants also mention the development of liberated companies, or teal organizations, that transform pyramidal and bureaucratic hierarchies into fluid, efficient systems of distributed authority and collective intelligence (Getz, 2009; Laloux, 2014).…”
Section: Defining Core Values For Responsible Managementmentioning
confidence: 99%
“…Some participants feel that diversity should be part of a global policy that is integrated and institutionalized as well as interdepartmental and horizontal—which is to say, collectively borne and implemented in a decentralized manner (Lee-Gosselin et al, 2013). Secondly, participants see solidarity in initiatives intended to democratize the economy through citizen action, particularly local agriculture, fair trade, or solidarity-based financing (Kalogeraki et al, 2018). Thirdly, participants also mention the development of liberated companies, or teal organizations, that transform pyramidal and bureaucratic hierarchies into fluid, efficient systems of distributed authority and collective intelligence (Getz, 2009; Laloux, 2014).…”
Section: Defining Core Values For Responsible Managementmentioning
confidence: 99%
“…In factm in the last 15 years, the SSE has brought about a 20% increase in employment (MonzoB n & Chaves, 2016). In a comparative study, Kalogeraki, Papadaki, & Pera Ros, (2018) compare the response of the SSE to the economic crisis in three European countries. Greece, strongly affected by the crisis and with little tradition in SSE, experienced a strong expansion in this type of organization in response to the social and economic needs that were not being addressed by the State.…”
Section: The Social and Solidarity Economy As An Opportunity?mentioning
confidence: 99%
“…Even though such organizations are discussed in the recent literature of sustainability [50,51], there is a lack of systematic comparative analyses documenting the extent to which these organizations are environmentally active in European countries or how these may promote resilience in the context of the crisis. It has been shown that those South European countries harder hit by the crisis-Greece and Spain-witnessed higher peaks in newly created alternative organizations and groups, while at the same time, their initiatives tended to be organized more frequently by informal and protest groups compared to those in the other countries [19,52,53]. According to the theories and prior research relating the economic crisis to the declining support for environmentalism [7], one would also expect that in such countries AAOs would not be as concerned for the environment as those in the countries least affected by the economic crisis (e.g., Germany or Sweden).…”
Section: Literature Review: Solidarity and Environmental Activism During Hard Timesmentioning
confidence: 99%